2022
DOI: 10.1200/jco.22.00501
|View full text |Cite
|
Sign up to set email alerts
|

Introducing Clinical Trial Updates

Abstract: I didn't have time to write a short letter, so I wrote a long one instead.-Mark TwainInitially reported in Journal of Clinical Oncology in 2019, 1 the ARCHES trial compared the addition of enzalutamide or placebo with androgen deprivation therapy (ADT) in men with metastatic hormone-sensitive prostate cancer (mHSPC). Enzalutamide significantly prolonged radiographic progression-free survival and prostate-specific antigen progression; overall survival (OS) data were immature. That report immediately changed cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…In our review of trials in advanced/metastatic setting that reported OS as a secondary end point, we found substantial variation in methodology for OS reporting and many trials lacked or deviated from the prespecified plan for OS reporting. Although there may be some reluctance from journals to publish secondary analyses, we note the recently introduced Clinical Trial Updates section of this Journal 33 should help with this situation. Publication of mature OS results is especially important for trials that were initially reported as positive in the primary publication.…”
Section: Discussionmentioning
confidence: 98%
“…In our review of trials in advanced/metastatic setting that reported OS as a secondary end point, we found substantial variation in methodology for OS reporting and many trials lacked or deviated from the prespecified plan for OS reporting. Although there may be some reluctance from journals to publish secondary analyses, we note the recently introduced Clinical Trial Updates section of this Journal 33 should help with this situation. Publication of mature OS results is especially important for trials that were initially reported as positive in the primary publication.…”
Section: Discussionmentioning
confidence: 98%
“…The publishing redesign joins other recent enhancements, including the introduction of the Clinical Trial Updates 1 and living guidelines 2 article types, visual abstracts, revamped podcasts, and a greater social media presence, all of which were informed by our strategic plan. 3 In keeping with the expanding breadth of research in oncology, we have highlighted our vision to expand the scope of published content to include economic analyses, 4 cutting-edge epidemiological studies, and studies using artificial intelligence techniques.…”
mentioning
confidence: 98%